Penerapan Pendekatan Realistik Bersetting Pembelajaran Kooperatif Tipe TAI Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V SD Inp 6/75 Manurungge Watampone Kab. Bone - muh idris jafar; rahma patta; hasbi rauf (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2018)
This research is a classroom action research conducted in two cycles with each cycle consisting of 3 meetings. Each cycle passes through several stages in each cycle, ie planning, execution, observation and evaluation, reflection. The purpose of this study is to determine the application of realsitic approach bersetting cooperative learning type Times Assissted Individualization (TAI) to improve student learning outcomes of grade V SD Inp 6/75 Manurungge Watampone Kab. Bone. The subjects of this study are the students of grade V SD, amounting to 23 people. Data collection techniques used are the test results of student learning conducted at the end of the cycle, the observation sheet and reflection. The collected data were analyzed using quantitative and qualitative analysis. The result of quantitative analysis shows that there is an increase of learning outcomes seen from the average score of students' mathematics learning outcomes are in the low category in cycle I while in cycle II is in very high category. Quantitatively there is an increase in the activity and motivation of students to learn mathematics. In this approach the students themselves construct or discover themselves from the concept of the given material. The teacher in this study acts as a facilitator in providing guidance and scatfolding. So, learning turns into student centered learning. Based on the results of this study can be concluded that the learning of mathematics through the application of realistic approach bersetting cooperative learning type TAI can improve the results of learning mathematics students of class V SD.